Towards Improving Sustainability in Nags Head, North Carolina Through Increasing Social Capital - Prescott, Nathalie (Consilience, 2011)
Maintaining bodies of knowledge specific to coastal towns can be crucial to maintaining environmental sustainability. It can build relationships of trust while generating social norms and rules about how to interact with the surrounding environment. This report explores the disintegration of social capital in Nags Head, North Carolina over time and how improving the transfer of local knowledge in the town can help to generate sustainable growth in the future. The researchers interviewed past residents of the town to gather information about how people used to interact with the environment in order to compare it to the present. Nine resources were explored; this report focuses on the resource of knowledge and its transfer.